Treasure Houses of the Book Arts in Germany - Halbey, Hans Adolf,Raabe, Paul,Scheffler, Christian (In:Fine print;San Francisco, Calif. : Pro Arte Libri, 1975;12(1986), 2, Seite 110-112, 1986)
Hans A. Halbey: Gutenberg Museum - Christian Scheffler: Klingspor Museum - Paul Raabe: Herzog August Bibliothek
Keywords: Deutschland; Buchkunst; Museum; Sammlung